Hepatic involvement in COVID 19 infection - Jayanta Paul (Archives of Hepatitis Research - Peertechz Publications, 2020)
Background: Severe Acute Respiratory Distress Syndrome Coronavirus -2 (SARS -CoV-2) outbreak is a significant public health threat since December 2019. Lung is the most common organ involved by COVID 19 followed by gastrointestinal tract and liver. This review article discusses hepatic involvement and monitoring in this outbreak.  Methods: Recently published studies from PubMed, Red Cross, and Copernicus were reviewed to prepare this review article.  Conclusions: Hepatic involvement is common in COVID 19 infection and it is the second most common organ involved after lung. Most of the hepatic involvements are mild and self limiting. However close monitoring is required.